Importância da tiorredoxina-1 nos efeitos citotóxicos diferenciais dos s-nitrosotióis-aril-butanamidas sobre linhagens celulares humanas normais e de carcinoma mamário - Fugimoto, Mariana [UNIFESP] (2019)
Female breast cancer is the one that affects most women worldwide, and it is classified according to the estrogen receptor (ER) expression, with ER- tumors being more aggressive and having worse prognosis. Nitric oxide (NO) is a gaseous free radical produced by organisms distributed through all phyla, acting as a signaling mediator in various cell types. NO-mediated cellular signaling occurs through post-translational modifications in proteins, responsible for physiological as well as pathological mechanisms. The manipulation of endogenous NO concentrations through administration of NO donors would be an interesting and viable method of therapy, with unexplored therapeutic potential. In physiological conditions, cells remain in a reducing environment, and its redox balance is maintained by antioxidant systems, such as the Thioredoxin-1 system (Trx-1), which has been shown to be overexpressed in several cancers and associated with aggressive tumor growth, resistance to conventional therapies, and decreased survival rates. Trx-1 is an appropriate molecular target for the study of the regulation of these processes, as well as in the development of new compounds that aim to alter the availability of this protein and of cell oxidants that may alter the cellular environment. Purpose: The objective of this study was to test the susceptibility of different cell lines to concentrations of S-nitrosothiols ortho and meta-chloro-SNOKs, in order to characterize them as compounds with antitumor activity that would exert their cytotoxic action preferentially on tumor cell lines. Methods: Four cell lines were used - two human breast cancer cell lines, one ER+ (MCF-7) and one ER- (MDA-MB-231); and two normal human mammary cell lines (HUVEC and MCF-10A). All cell lines were tested for viability assays, measurement of intra- and extracellular NO concentrations, cell death verification, and expression level of Pro-Caspase 3, PARP, cleaved PARP and Trx-1 proteins. Results: Differential toxicity of SNOKs to tumor lineages was demonstrated in cell viability assays and cell death assay. These results were correlated with higher intra and extracellular NO concentrations found in the tumor cell lines after incubation with the compounds. Differential toxicity was related to an xxiv apoptotic process due to a lower expression of Pro-Caspase 3 and Trx-1 proteins, and presence of cleavage of PARP protein. Conclusion: The studied compounds stimulate proliferation and/or maintain cell viability in the tumor cell lines when incubated at low concentrations, while inducing cell death at higher concentrations. These compounds presented molecular characteristics that make them as potential chemotherapeutic agents in the treatment of several types of cancer. Given the relevance of the results and potential chemotherapy to be explored further investigation of the mechanisms and pathways presented here would be of great clinical relevance in the future.